2019
DOI: 10.17265/1539-8072/2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of STEM Tinkering Approaches in Primary School Education in Greece

Abstract: In this paper, they are presented the experiences that emerged from the implementation of STEM approaches in primary education in Greece, given the context in which schools operate. The aim is to stimulate discussion on the possibilities and feasibility of introducing STEM activities in Greek schools. Two public schools in Attica were selected as pilot schools to test the proposal in which eight different actions were implemented in different grades.Indicatively, one of the actions implemented for nine classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Besides curriculum limitations and poor expertise for STEAM implementation, other difficulties reported in all six countries are the lack of infrastructure and proper educational materials. STEAM education requires schools to have a series of bespoke platforms, tools, pedagogical material, and a sizeable budget [47]. Primary school and preschool teachers in Türkiye and Romania suggested overcoming these difficulties, with parents' help, and this brings up the question for the potential of school-family partnerships as a formal support strategy for STEAM implementation at all education levels in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…Besides curriculum limitations and poor expertise for STEAM implementation, other difficulties reported in all six countries are the lack of infrastructure and proper educational materials. STEAM education requires schools to have a series of bespoke platforms, tools, pedagogical material, and a sizeable budget [47]. Primary school and preschool teachers in Türkiye and Romania suggested overcoming these difficulties, with parents' help, and this brings up the question for the potential of school-family partnerships as a formal support strategy for STEAM implementation at all education levels in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the Greek educational system, the research findings showed that there is no utilization of new and innovative educational methods such as CT and STEM, while it lags behind in the use of new technologies (information and communication technologies). This may be because the education system is structured based on a centralized design followed by all schools, leaving little autonomy in the school units [ 48 ]. However, recent research in Greece shows that there is some positive dynamics at least in the integration of STEM in education [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in Greece, the education system is structured based on a centralized design followed by all schools, leaving little autonomy in the school units. The curricula are common to all schools and are taught by specific textbooks [ 48 ]. In the last quarter of 2017, the Educational Policy Institute (IEP) as national coordinator for Greece of the European Project H2020: “Open Schools for Open Societies (OSOS)”, advanced a call for school units to participate in the pilot phase of the OSOS project which has been implemented since the 2017–2018 school year.…”
Section: Introductionmentioning
confidence: 99%
“…In the Current situation in Greece in STEM / STEAM -School curricula axis, it is reflected that STEM education has not been formally introduced in the curricula, while the efforts recorded so far are made mainly through pilot programs. Several studies have highlighted the effectiveness of the STEM approach in improving the educational process (Smyrnaiou, Petropoulou, Sotiriou, 2015;IEP, 2017;Kotsifakos, Kostis, Douligeris, 2017;Psyharis, 2018;Patrinopoulos, Iatrou, 2019;Psycharis, Kotzampasaki).…”
Section: Research Methods and Findingsmentioning
confidence: 99%
“…are some of what was studied (Patrinopoulos, 2017;Patrinopoulos, Kefalis, 2017;IEP, 2017;EELLAK, 2021). However, despite the increasing dynamics in the introduction of STEM in the educational process, it is found that the implementation of activities is fragmented and isolated, without systematic and long-term implementation in schools (Patrinopoulos, Iatrou, 2019).…”
Section: Research Methods and Findingsmentioning
confidence: 99%